REVIEW OF SYNCHRONIZATION OF TURBOGENRATORS - OKPIGHE, SUNDAY OKEREKEHE; CHARLES MONYE; JAMES EJENIKE OGAGAROJO OVRI (IJRDO - Journal of Mechanical And Civil Engineering, 2019)
A Review of  Synchronization of Turbo-generators is reported.  Factors and criteria  for effective and efficient synchronization have been highlighted. Consequences of poor synchronization have been enumerated. The  role and benefits of synchronization in the scheme of the power grid system has been emphasized